2016
DOI: 10.1248/bpb.b16-00264
|View full text |Cite|
|
Sign up to set email alerts
|

Cargo-Free Nanoparticles Containing Cationic Lipids Induce Reactive Oxygen Species and Cell Death in HepG2 Cells

Abstract: These effects were dependent on the lipid concentration, surface density of cationic lipids, and particle size of NPs. However, neutral NPs consisting of 1,2-dioleoyl-3-phosphocholine did not elicit the effective ROS generation or cell death regardless of the lipid concentration and particle size. The present study suggests that DOTAP-and DOTMA-NPs are able to induce cancer cell death through production of ROS in the absence of any therapeutic cancer reagents. These results also provide a rational background f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…To test this possibility, DOPE was incorporated into cargo‐free cNP up to 30 mol% at the expense of DOTAP and the DOPE‐cNP were treated with cells. However, ROS levels were somewhat lower than those observed after treatment with DOPE‐free cNP (results not shown), which was already suggested previously (Yun et al, ). Although the overall results in this study did not provide any evidence that explained the contrasting effect of DOPE on ROS induction, this discrepancy may be attributable to the different potency of DAG and DOPE in the promotion of the nonlamellar phase in membranes.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…To test this possibility, DOPE was incorporated into cargo‐free cNP up to 30 mol% at the expense of DOTAP and the DOPE‐cNP were treated with cells. However, ROS levels were somewhat lower than those observed after treatment with DOPE‐free cNP (results not shown), which was already suggested previously (Yun et al, ). Although the overall results in this study did not provide any evidence that explained the contrasting effect of DOPE on ROS induction, this discrepancy may be attributable to the different potency of DAG and DOPE in the promotion of the nonlamellar phase in membranes.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, these results indicate that cationic lipid‐induced ROS generation in cells is closely related to cell viability, and that DAG in cNP enhances the ROS‐mediated cell death. In addition, these results suggested that although a positive charge in cNP is important in ROS production and death of cancer cells (Yun et al, ), other factors such as specific lipid compositions and/or the physicochemical properties of cNP are also involved in cytotoxicity, as mentioned above. Similar to the results shown in Fig.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Compared with viral vectors, transfection efficiency (TE) of cationic liposomes is low and clinically insufficient. One reason for this is reactive oxygen species (ROS) generation, which induces cytotoxicity (Yun et al, 2016) and affects intracellular signaling pathways (Mikhed et al, 2015). It has been suggested that the cytotoxicity of cationic carriers, especially 1,2-dioleoyl-3-trimethylammonium-propane (DOTAP)based cationic liposomes, is caused by ROS generation.…”
Section: Introductionmentioning
confidence: 99%